b-Quark Physics with the LEP Collider The Development of Experimental Techniques for b-Quark Studies from Z^0-Decay - Barker, Gary John (Springer Tracts in Modern Physics, 2010)
The book reviews the unexpected impact that the LEP experiments have had on the subject of b-quark physics. The emphasis is firmly on telling the story from an experimental viewpoint. Aspects of the detectors that were essential for the reconstruction of b-hadrons are highlighted, especially the role played by silicon strip detectors and particle identification methods. The importance of solving practical issues such as detector alignment and track reconstruction to fully realize the reconstruction potential of the detectors is demonstrated along with various examples of potential problems when these aspects are not well controlled. Barker details new ideas and analysis techniques that evolved during the years of LEP running so that the information is useful to new researchers or those putting together plans for future b-physics experiments. Highlights of the final b-physics results from the LEP collaborations are reviewed in the context of results from other experiments around the world and with respect to what we learn about the Standard Model of Particle Physics.